An Amplicon Panel for High-Throughput and Low-Cost Genotyping of Yesso Scallop Mizuhopecten yessoensis - Ben J. G. Sutherland; Chen Yin Walker; Denman Moody; Chelsea Bennett; Marissa Wright-LaGreca; Chloe Shamash-McLaughlin; Karen Leask; Daniel Roth; Megan Lebeuf; Timothy J. Green (Marine Biotechnology, 2026)

Ambipolar electric field-driven ionospheric upflow and event duration analysis during IPY-ESR 2007 - Timothy Wemimo David; Emmanuel O. Adetunji; Chizurumoke M. Michael; Darren Moody Wright; Adetoro Temitope Talabi; Abayomi Ekundayo Ajetunmobi (Advances in Space Research, 2026)

Vocal development and patterns of vocal variation inform conservation of a critically endangered macaw - Alexander G. Allison; Mario Jimenez; Timothy F. Wright (Animal Behaviour, 2026)

Nocturnal flight call monitoring reveals in-flight behavioral alteration by avian migrants in response to artificial light at night - Dylan M. Osterhaus; Kelley C. Boland; Abigail J. Lawson; Kyle G. Horton; Benjamin M. Van Doren; Patricia L. Cutler; Timothy F. Wright; Martha J. Desmond (Biological Conservation, 2025)

Comparison of Branched DNA to RT-qPCR Technology for the Quantitation of mRNA from mRNA-LNP Drug Product in Human Serum - Carl A. Luongo; Ashley D. Wright; Timothy L. Lochmann; Sweilem B. Al Rihani; Jean-Claude Marshall; Darshana Jani; Jason Pennucci; Jessica Ortiz (The AAPS Journal, 2025)

Differential survival of Ilyanassa obsoleta to water temperature and association with the non-native red alga Gracilaria vermiculophylla - Timothy S. Lee; Amy E. Fowler; Jessica R. Largen; Jonathan P. Russo; Zackary J. Schlegel; Dawson K. Wright; April M. H. Blakeslee (Hydrobiologia, 2025)
Along the U.S. east coast, the widespread non-native red alga Gracilaria vermiculophylla provides habitat for an array of macroinvertebrates, including the eastern mudsnail Ilyanassa obsoleta . Though I. obsoleta tolerates a wide temperature range, increases in summer water temperatures may enhance mortality; furthermore, the presence of non-native algae in rising seawater temperatures could exacerbate harmful conditions. We tested how the presence or absence of G. vermiculophylla influenced snail mortality across a range of summer temperatures over a 3-week period. We found that I. obsoleta survived the longest in the lowest temperature (27 °C), followed by the medium (32 °C), and lastly the highest (36 °C) where all snails died within 2 days. Mortality was also higher and faster for snails in the presence versus absence of G. vermiculophylla . We suspected dissolved oxygen became very low at the higher temperatures with G. vermiculophylla ; thus we conducted a laboratory-based dissolved oxygen experiment. We found that G. vermiculophylla degraded and oxygen declined faster at the highest temperature treatment, thereby creating anoxic conditions. Altogether, our results demonstrate that G. vermiculophylla could enhance anoxic conditions at high summer temperatures, potentially leading to enhanced faunal mortality.

Phytoremediation evaluation of forever chemicals using hemp (Cannabis sativa L.): Pollen bioaccumulation and the risk to bees - Timothy Wright; Marcus Crompton; Daniel Bishop; Glen Currell; Laxmi Suwal; Brett D. Turner (Chemosphere, 2025)

Bridging knowledge gaps in human chemical exposure via drinking water with non-target screening - Davide Ciccarelli; Saer Samanipour; Helena Rapp-Wright; Stefan Bieber; Thomas Letzel; Jake W. O’Brien; Tim Marczylo; Timothy W. Gant; Paolo Vineis; Leon P. Barron (Critical Reviews in Environmental Science and Technology, 2025)

Threat assessment for Pacific sand lance (Ammodytes personatus) in the Salish Sea - Jacqueline R. Huard; Victoria Hemming; Matthew R. Baker; Jennifer Blancard; Ian Bruce; Sarah Cook; Gail K. Davoren; Phillip Dionne; Virginia East; J. Mark Hipfner; Nicola R. Houtman; Brian A. Koval; et al. (Frontiers in Marine Science, 2024)
Like many forage fish species, Pacific sand lance ( Ammodytes personatus ) play a key role in nearshore marine ecosystems as an important prey source for a diverse array of predators in the northeastern Pacific. However, the primary threats to Pacific sand lance and their habitat are poorly defined due to a lack of systematic data. Crucial information needed to assess their population status is also lacking including basic knowledge of their local and regional abundance and distribution. Sand lance are currently listed as ‘not evaluated’ under the IUCN red list and they have not been assessed by US and Canadian agencies. This hampers management and policy efforts focused on their conservation. To address this knowledge gap, we conducted a three-part, structured expert elicitation to assess the vulnerability of Salish Sea sand lance populations. Experts were asked to list and rank key threats to Salish Sea sand lance and/or their habitat, to further quantify the vulnerability of sand lance to identified threats using a vulnerability matrix, and to predict the population trajectory in 25 years from today. Impacts associated with climate change (e.g. sea level rise, sea temperature rise, ocean acidification, and extreme weather) consistently ranked high as threats of concern in the ranking exercise and quantified vulnerability scores. Nearly every expert predicted the population will have declined from current levels in 25 years. These results suggest sand lance face numerous threats and may be in decline under current conditions. This research provides vital information about which threats pose the greatest risk to the long-term health of sand lance populations and their habitat. Managers can use this information to prioritize which threats to address. Future research to reliably quantify population size, better understand the roles of natural and anthropogenic impacts, and to identify the most cost-effective actions to mitigate multiple threats, is recommended.

Advancing Understanding of Chemical Exposures and Maternal-child Health Through the U.S. Environmental Influences on Child Health Outcomes (ECHO) Program: A Scoping Review - Emily S. Barrett; Jennifer L. Ames; Stephanie M. Eick; Alicia K. Peterson; Zorimar Rivera-Núñez; Anne P. Starling; Jessie P. Buckley; Barbara O‟Brien; Lisa Peterson; Patrick Parsons; Kannan Kurunthacalam; Manish Arora; et al. (Current Environmental Health Reports, 2024)
Purpose of Review Environmental chemical exposures may disrupt child development, with long-lasting health impacts. To date, U.S. studies of early environmental exposures have been limited in size and diversity, hindering power and generalizability. With harmonized data from over 60,000 participants representing 69 pregnancy cohorts, the National Institutes of Health’s Environmental influences on Child Health Outcomes (ECHO) Program is the largest study of U.S. children’s health. Here, we: (1) review ECHO-wide studies of chemical exposures and maternal-child health; and (2) outline opportunities for future research using ECHO data. Recent Findings As of early 2024, in addition to over 200 single-cohort (or award) papers on chemical exposures supported by ECHO, ten collaborative multi-cohort papers have been made possible by ECHO data harmonization and new data collection. Multi-cohort papers have examined prenatal exposure to per- and polyfluoroalkyl substances (PFAS), phthalates, phenols and parabens, organophosphate esters (OPEs), metals, melamine and aromatic amines, and emerging contaminants. They have primarily focused on describing patterns of maternal exposure or examining associations with maternal and infant outcomes; fewer studies have examined later child outcomes (e.g., autism) although follow up of enrolled ECHO children continues. The NICHD’s Data and Specimen Hub (DASH) database houses extensive ECHO data including over 470,000 chemical assay results and complementary data on priority outcome areas (pre, peri-, and postnatal, airway, obesity, neurodevelopment, and positive health), making it a rich resource for future analyses. Summary ECHO’s extensive data repository, including biomarkers of chemical exposures, can be used to advance our understanding of environmental influences on children’s health. Although few published studies have capitalized on these unique harmonized data to date, many analyses are underway with data now widely available.

Natural selection on feralization genes contributed to the invasive spread of wild pigs throughout the United States - Niek W. G. Barmentlo; Patrick G. Meirmans; William H. Stiver; Joseph G. Yarkovich; Blake E. McCann; Antoinette J. Piaggio; Dominic Wright; Timothy J. Smyser; Mirte Bosse (Molecular Ecology, 2024)
Despite a long presence in the contiguous United States (US), the distribution of invasive wild pigs ( Sus scrofa × domesticus ) has expanded rapidly since the 1980s, suggesting a more recent evolutionary shift towards greater invasiveness. Contemporary populations of wild pigs represent exoferal hybrid descendants of domestic pigs and European wild boar, with such hybridization expected to enrich genetic diversity and increase the adaptive potential of populations. Our objective was to characterize how genetic enrichment through hybridization increases the invasiveness of populations by identifying signals of selection and the ancestral origins of selected loci. Our study focused on invasive wild pigs within Great Smoky Mountains National Park, which represents a hybrid population descendent from the admixture of established populations of feral pigs and an introduction of European wild boar to North America. Accordingly, we genotyped 881 wild pigs with multiple high‐density single‐nucleotide polymorphism (SNP) arrays. We found 233 markers under putative selection spread over 79 regions across 16 out of 18 autosomes, which contained genes involved in traits affecting feralization. Among these, genes were found to be related to skull formation and neurogenesis, with two genes, TYRP1 and TYR, also encoding for crucial melanogenesis enzymes. The most common haplotypes associated with regions under selection for the Great Smoky Mountains population were also common among other populations throughout the region, indicating a key role of putatively selective variants in the fitness of invasive populations. Interestingly, many of these haplotypes were absent among European wild boar reference genotypes, indicating feralization through genetic adaptation.

Dose selection for aztreonam-avibactam, including adjustments for renal impairment, for Phase IIa and Phase III evaluation - Shampa Das; Todd Riccobene; Timothy J. Carrothers; James G. Wright; Merran MacPherson; Andrew Cristinacce; Lynn McFadyen; Rujia Xie; Alison Luckey; Susan Raber (European Journal of Clinical Pharmacology, 2024)
Purpose A series of iterative population pharmacokinetic (PK) modeling and probability of target attainment (PTA) analyses based on emerging data supported dose selection for aztreonam-avibactam, an investigational combination antibiotic for serious Gram-negative bacterial infections. Methods Two iterations of PK models built from avibactam data in infected patients and aztreonam data in healthy subjects with “patient-like” assumptions were used in joint PTA analyses (primary target: aztreonam 60% f T > 8 mg/L, avibactam 50% f T > 2.5 mg/L) exploring patient variability, infusion durations, and adjustments for moderate (estimated creatinine clearance [CrCL] > 30 to ≤ 50 mL/min) and severe renal impairment (> 15 to ≤ 30 mL/min). Achievement of > 90% joint PTA and the impact of differential renal clearance were considerations in dose selection. Results Iteration 1 simulations for Phase I/IIa dose selection/modification demonstrated that 3-h and continuous infusions provide comparable PTA; avibactam dose drives joint PTA within clinically relevant exposure targets; and loading doses support more rapid joint target attainment. An aztreonam/avibactam 500/137 mg 30-min loading dose and 1500/410 mg 3-h maintenance infusions q6h were selected for further evaluation. Iteration 2 simulations using expanded PK models supported an alteration to the regimen (500/167 mg loading; 1500/500 mg q6h maintenance 3-h infusions for CrCL > 50 mL/min) and selection of doses for renal impairment for Phase IIa/III clinical studies. Conclusion A loading dose plus 3-h maintenance infusions of aztreonam-avibactam in a 3:1 fixed ratio q6h optimizes joint PTA. These analyses supported dose selection for the aztreonam-avibactam Phase III clinical program. Clinical trial registration : NCT01689207; NCT02655419; NCT03329092; NCT03580044.

A critical review of microplastics toxicity and potential adverse outcome pathway in human gastrointestinal tract following oral exposure - Lorna R. Jones; Stephanie J. Wright; Timothy W. Gant (Toxicology Letters, 2023)

Quantifying risks avoided by limiting global warming to 1.5 or 2 °C above pre-industrial levels - Rachel Warren; Oliver Andrews; Sally Brown; Felipe J. Colón-González; Nicole Forstenhäusler; David E. H. J. Gernaat; P. Goodwin; Ian Harris; Yi He; Chris Hope; Desmond Manful; Timothy J. Osborn; et al. (Climatic Change, 2022)
The Paris Agreement aims to constrain global warming to ‘well below 2 °C’ and to ‘pursue efforts’ to limit it to 1.5 °C above pre-industrial levels. We quantify global and regional risk-related metrics associated with these levels of warming that capture climate change–related changes in exposure to water scarcity and heat stress, vector-borne disease, coastal and fluvial flooding and projected impacts on agriculture and the economy, allowing for uncertainties in regional climate projection. Risk-related metrics associated with 2 °C warming, depending on sector, are reduced by 10–44% globally if warming is further reduced to 1.5 °C. Comparing with a baseline in which warming of 3.66 °C occurs by 2100, constraining warming to 1.5 °C reduces these risk indicators globally by 32–85%, and constraining warming to 2 °C reduces them by 26–74%. In percentage terms, avoided risk is highest for fluvial flooding, drought, and heat stress, but in absolute terms risk reduction is greatest for drought. Although water stress decreases in some regions, it is often accompanied by additional exposure to flooding. The magnitude of the percentage of damage avoided is similar to that calculated for avoided global economic risk associated with these same climate change scenarios. We also identify West Africa, India and North America as hotspots of climate change risk in the future.

Globally, tree fecundity exceeds productivity gradients - Valentin Journé; Robert Andrus; Marie‐Claire Aravena; Davide Ascoli; Roberta Berretti; Daniel Berveiller; Michal Bogdziewicz; Thomas Boivin; Raul Bonal; Thomas Caignard; Rafael Calama; Jesús Julio Camarero; et al. (Ecology Letters, 2022)
Lack of tree fecundity data across climatic gradients precludes the analysis of how seed supply contributes to global variation in forest regeneration and biotic interactions responsible for biodiversity. A global synthesis of raw seedproduction data shows a 250‐fold increase in seed abundance from cold‐dry to warm‐wet climates, driven primarily by a 100‐fold increase in seed production for a given tree size. The modest (threefold) increase in forest productivity across the same climate gradient cannot explain the magnitudes of these trends. The increase in seeds per tree can arise from adaptive evolution driven by intense species interactions or from the direct effects of a warm, moist climate on tree fecundity. Either way, the massive differences in seed supply ramify through food webs potentially explaining a disproportionate role for species interactions in the wet tropics.

Madagascar Terrestrial Camera Survey Database 2021: A collation of protected forest camera surveys from 2007–2021 - Erin M. Wampole; Brian D. Gerber; Zach J. Farris; Jean Claude Razafimahaimodison; Mahandry Hugues Andrianarisoa; Claude Jacquot Ralazampirenena; Patricia C. Wright; C. Delaid Rasamisoa; Dean Gibson; Mathias W. Tobler; Timothy M. Eppley; Natalie Vasey; et al. (Ecology, 2022)
Madagascar is a threatened global biodiversity hotspot and conservation priority, yet we lack broad‐scale surveys to assess biodiversity across space and time. To fill this gap, we collated camera trap surveys, capturing species occurrences within Madagascar into a single standardized database. This data set includes nine distinct protected areas of Madagascar and encompasses 13 subprojects, 38 camera arrays, and 1156 sampling units (independent camera site per survey) within two important biodiversity eco‐regions: western dry deciduous forest and eastern humid rainforest. Camera surveys were conducted from June 2007 to January 2021. The final data set includes 17 unique families of mammals (Bovidae, Canidae, Cheirogaleidae, Daubentoniidae, Equidae, Eupleridae, Felidae, Hominidae, Indriidae, Lemuridae, Lepilemuridae, Muridae, Nesomyidae, Pteropodidae, Soricidae, Suidae, Tenrecidae) comprising 45 species and 27 unique families of birds (Accipitridae, Acrocephalidae, Alcedinidae, Bernieridae, Brachypteraciidae, Caprimulgidae, Cisticolidae, Columbidae, Coraciidae, Corvidae, Cuculidae, Dicruridae, Mesitornithidae, Monarchidae, Motacillidae, Muscicapidae, Numididae, Phasianidae, Rallidae, Sarothruridae, Strigidae, Sturnidae, Sulidae, Threskiornithidae, Upupidae, Vangidae, Zosteropidae) comprising 58 species. Images were processed and verified by individual project data set creators and camera operation and species tables were then collated. The final product represents the first broad‐scale freely available standardized formal faunal database for Madagascar. Data are available through this publication and at DOI: 10.5281/zenodo.5801806. These data will be useful for examining species‐level and community‐level trends in occurrence across space or time within Madagascar and globally, evaluating native and invasive species dynamics, and will aid in determining species conservation status and planning for at‐risk species. There are no copyright restrictions; please cite this paper when using the data for publication.

Combined effect of alcohol and cannabis on simulated driving - Andrew Fares; Christine M. Wickens; Robert E. Mann; Patricia Di Ciano; Madison Wright; Justin Matheson; Omer S. M. Hasan; Jurgen Rehm; Tony P. George; Andriy V. Samokhvalov; Paul A. Shuper; Marilyn A. Huestis; et al. (Psychopharmacology, 2022)

An Evaluation of the Performance of Sea Ice Thickness Forecasts to Support Arctic Marine Transport - Tarkan Aslan Bilge; Nicolas Fournier; Davi Mignac; Laura Hume-Wright; Laurent Bertino; Timothy Williams; Steffen Tietsche (Journal of Marine Science and Engineering, 2022)
In response to declining sea ice cover, human activity in the Arctic is increasing, with access to the Arctic Ocean becoming more important for socio-economic reasons. Accurate knowledge of sea ice conditions is therefore becoming increasingly important for reducing the risk and operational cost of human activities in the Arctic. Satellite-based sea ice charting is routinely used for tactical ice management, but the marine sector does not yet make optimal use of sea ice thickness (SIT) or sea ice concentration (SIC) forecasts on weekly timescales. This is because forecasts have not achieved sufficient accuracy, verification and resolution to be used in situations where maritime safety is paramount, and assessing the suitability of forecasts can be difficult because they are often not available in the appropriate format. In this paper, existing SIT forecasts currently available on the Copernicus Marine Service (CMS) or elsewhere in the public domain are evaluated for the first time. These include the seven-day forecasts from the UK Met Office, MET Norway, the Nansen Environmental and Remote Sensing Center (NERSC) and the European Centre for Medium-Range Weather Forecasts (ECMWF). Their forecast skills were assessed against unique in situ data from five moorings deployed between 2016 and 2019 by the Barents Sea Metocean and Ice Network (BASMIN) and Barents Sea Exploration Collaboration (BaSEC) Joint Industry Projects. Assessing these models highlights the importance of data assimilation in short-term forecasting of SIT and suggests that improved assimilation of sea ice data could increase the utility of forecasts for navigational purposes. This study also demonstrates that forecasts can achieve similar or improved correlation with observations when compared to a persistence model at a lead time of seven days, providing evidence that, when used in conjunction with sea ice charts, SIT forecasts could provide valuable information on future sea ice conditions.

Ocean Acidification Alters Developmental Timing and Gene Expression of Ion Transport Proteins During Larval Development in Resilient and Susceptible Lineages of the Pacific Oyster (Crassostrea gigas) - Marissa Wright-LaGreca; Clara Mackenzie; Timothy J. Green (Marine Biotechnology, 2022)

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Effects of life history and reproduction on recruitment time lags in reintroductions of rare plants - Matthew A. Albrecht; Oyomoare L. Osazuwa‐Peters; Joyce Maschinski; Timothy J. Bell; Marlin L. Bowles; William E. Brumback; Janice Duquesnel; Michael Kunz; Jimmy Lange; Kimberlie A. McCue; A. Kathryn McEachern; Sheila Murray; et al. (Conservation Biology, 2019)
Reintroductions are important components of conservation and recovery programs for rare plant species, but their long‐term success rates are poorly understood. Previous reviews of plant reintroductions focused on short‐term (e.g., ≤3 years) survival and flowering of founder individuals rather than on benchmarks of intergenerational persistence, such as seedling recruitment. However, short‐term metrics may obscure outcomes because the unique demographic properties of reintroductions, including small size and unstable stage structure, could create lags in population growth. We used time‐to‐event analysis on a database of unusually well‐monitored and long‐term (4–28 years) reintroductions of 27 rare plant species to test whether life‐history traits and population characteristics of reintroductions create time‐lagged responses in seedling recruitment (i.e., recruitment time lags [RTLs]), an important benchmark of success and indicator of persistence in reintroduced populations. Recruitment time lags were highly variable among reintroductions, ranging from

Juvenile root vigour improves phosphorus use efficiency of potato - Philip J. White; John E. Bradshaw; Lawrie K. Brown; M. Finlay B. Dale; Lionel X. Dupuy; Timothy S. George; John P. Hammond; Nithya K. Subramanian; Jacqueline A. Thompson; Jane Wishart; Gladys Wright (Plant and Soil, 2018)

Retrofitting LID Practices into Existing Neighborhoods: Is It Worth It? - Timothy J. Wright; Yaoze Liu; Natalie J. Carroll; Laurent M. Ahiablame; Bernard A. Engel (Environmental Management, 2016)

Unstirred Water Layers and the Kinetics of Organic Cation Transport - Takahiro Shibayama; Mark Morales; Xiaohong Zhang; Lucy J. Martínez-Guerrero; Alfred Berteloot; Timothy W. Secomb; Stephen H. Wright (Pharmaceutical Research, 2015)

Shared genetic diversity across the global invasive range of the monk parakeet suggests a common restricted geographic origin and the possibility of convergent selection - Pim Edelaar; Severine Roques; Elizabeth A. Hobson; Anders Gonçalves da Silva; Michael L. Avery; Michael A. Russello; Juan C. Senar; Timothy F. Wright; Martina Carrete; José L. Tella (Molecular Ecology, 2015)
While genetic diversity is hypothesized to be an important factor explaining invasion success, there is no consensus yet on how variation in source populations or demographic processes affects invasiveness. We used mitochondrial DNA haplotypic and microsatellite genotypic data to investigate levels of genetic variation and reconstruct the history of replicate invasions on three continents in a globally invasive bird, the monk parakeet ( Myiopsitta monachus ). We evaluated whether genetic diversity at invasive sites could be explained by (i) the native source populations from which they were derived and (ii) demographic bottlenecks during introduction. Genetic data indicated a localized source area for most sampled invasive populations, with limited evidence for admixing of native source populations. This pattern largely coincides with historical data on pet trade exports. However, the invasive populations are genetically more similar than predicted from the export data alone. The extent of bottleneck effects varied among invasive populations. The observed low genetic diversity, evidence of demographic contraction and restricted source area do not support the hypothesis that invasion is favoured by the mixing and recombining of genetic variation from multiple source populations. Instead, they suggest that reduced genetic variation through random processes may not inhibit successful establishment and invasion in this species. However, convergent selection across invasive sites could also explain the observed patterns of reduction and similarity in genetic variation and/or the restricted source area. In general, the alternative explanation of intraspecific variation in invasive potential among genotypes or geographic areas is neglected, but warrants more attention as it could inform comparative studies and management of biological invaders.

How weed control and fertilisation influence tree physiological processes and growth at early establishment in an exotic F1 hybrid pine plantation of subtropical Australia - Paula T. Ibell; Zhihong H. Xu; Terence J. Blake; Carole Wright; Timothy J. Blumfield (Journal of Soils and Sediments, 2014)

A test of multiple hypotheses for the function of call sharing in female budgerigars, Melopsittacus undulatus - Christine R. Dahlin; Anna M. Young; Breanne Cordier; Roger Mundry; Timothy F. Wright (Behavioral Ecology and Sociobiology, 2014)

Priority research questions for the UK food system - John S. I. Ingram; Hugh L. Wright; Lucy Foster; Timothy Aldred; David Barling; Tim G. Benton; Paul M. Berryman; Charles S. Bestwick; Alice Bows-Larkin; Tim F. Brocklehurst; Judith Buttriss; John Casey; et al. (Food Security, 2013)
The rise of food security up international political, societal and academic agendas has led to increasing interest in novel means of improving primary food production and reducing waste. There are however, also many ‘post-farm gate’ activities that are critical to food security, including processing, packaging, distributing, retailing, cooking and consuming. These activities all affect a range of important food security elements, notably availability, affordability and other aspects of access, nutrition and safety. Addressing the challenge of universal food security, in the context of a number of other policy goals (e.g. social, economic and environmental sustainability), is of keen interest to a range of UK stakeholders but requires an up-to-date evidence base and continuous innovation. An exercise was therefore conducted, under the auspices of the UK Global Food Security Programme, to identify priority research questions with a focus on the UK food system (though the outcomes may be broadly applicable to other developed nations). Emphasis was placed on incorporating a wide range of perspectives (‘world views’) from different stakeholder groups: policy, private sector, non-governmental organisations, advocacy groups and academia. A total of 456 individuals submitted 820 questions from which 100 were selected by a process of online voting and a three-stage workshop voting exercise. These 100 final questions were sorted into 10 themes and the ‘top’ question for each theme identified by a further voting exercise. This step also allowed four different stakeholder groups to select the top 7–8 questions from their perspectives. Results of these voting exercises are presented. It is clear from the wide range of questions prioritised in this exercise that the different stakeholder groups identified specific research needs on a range of post-farm gate activities and food security outcomes. Evidence needs related to food affordability, nutrition and food safety (all key elements of food security) featured highly in the exercise. While there were some questions relating to climate impacts on production, other important topics for food security (e.g. trade, transport, preference and cultural needs) were not viewed as strongly by the participants.

Mosquitoes of North America with emphasis in the midwestern United States: long‐term occurrence patterns - Jessica J. Hellmann; Jason D. K. Dzurisin; Timothy Wright; David Cieslak; Samuel Pecoraro; Kaitlyn E. Smith; Katharine Hayhoe; Kerry L. Griffis-Kyle (Ecology, 2013)
Mosquitoes are ecologically and economically important invertebrates that transmit numerous diseases and are an integral part of the food web in many terrestrial and aquatic ecosystems. Despite their importance, there have been no central repositories for occurrence or abundance records of mosquitoes in the United States. To enable research dependent on the geographic distribution and abundance of mosquito species, we built a database of occurrence records collected by many individuals and agencies, primarily in the United States and with emphasis on unpublished data in the Midwest region. This resource is invaluable to researchers studying mosquito ecology, disease vectors and pathways, and insect pests. The database contains 542 144 occurrence records, and each record includes information on sex, life stage, sampling method, presence/absence or abundance, and date and location of sampling. The accessibility of this resource will directly impact management and planning for mosquito‐borne diseases with region‐specific or species‐specific modeling. Because there is little centralized ecological information on mosquitoes, this database is foundational to expanding knowledge of mosquito ecology.

Cryptic species in a Neotropical parrot: genetic variation within the Amazona farinosa species complex and its conservation implications - Theodore J. Wenner; Michael A. Russello; Timothy F. Wright (Conservation Genetics, 2012)

Large scale international replication and meta-analysis study confirms association of the 15q14 locus with myopia. The CREAM consortium - Virginie J. M. Verhoeven; Pirro G. Hysi; Seang-Mei Saw; Veronique Vitart; Alireza Mirshahi; Jeremy A. Guggenheim; Mary Frances Cotch; Kenji Yamashiro; Paul N. Baird; David A. Mackey; Robert Wojciechowski; M. Kamran Ikram; et al. (Human Genetics, 2012)

Forest Policy / Biosecurity - Linda Heath; Clark Row; Robert Perschel; Douglas Boucher; Patricia Elias; Katherine Lininger; Calen May-Tobin; Earl Saxon; Steven Ruddell; Sally Collins; Sarah Ruddell; Mo Zhou; et al. (Journal of Forestry, 2011)
7Massive fires in Indonesian peatlands in the 1990s and in eastern Russian peatlands in 2002 and last year have highlighted the need to manage forests overlying peat deposits, as well as converted peat forests and open peatlands. Peat or peaty soils, contain 65% or more of partially decayed vegetation, can burn freely or underground. They cover some 10 percent of worldwide forests and contain 25 percent of all terrestrial carbon. Recent massive greenhouse gas (GHG) emissions from fires in forested peat and peatland in Indonesia and in Russia highlight the need for policies to reduce GHG emissions. We discuss major peatland areas and quantify their carbon stocks and potential GHG emissions. Trends show that year-to-year emissions are variable, with huge pulses that are a significant share of global GHG emissions. We group suggested policy options into three approaches. The first approach, which will reduce peat-related product demand, includes a) restricting peat, and products produced on cleared forested peatland, from being labeled or counted in GHG reduction achievements, as renewable (which palm oil currently is considered); b) developing full substitutes for horticultural peat (comprising about half mined peat use); and c) developing renewable power in countries still dependent on peat for power generation. These options reduce the rate of developing newly mined peat/forest areas. Options for a second approach, which treat already drained and cleared forested peatlands, are: d) restoring functioning peat ecosystems by closing drainage ditches, allowing natural rewetting, and “seeding” with peat vegetation fragments, e) requiring current peat operators to restore mined areas right after all peat is removed, and f) converting them to other land uses, despite the acidic conditions of mined peat bogs. These options sharply reduce risks of peat fires. Finally, a third group of policy options reduces ignition risks and limit fire spread: g) developing monitoring, suppression techniques, h) organizing local landowner protection groups and i) improving public fire organizations.

The Federal Energy Regulatory Commission and the Minerals Management Service - Timothy Konnert; Wright Frank (Oceanography, 2010)

Differentially expressed genes during malting and correlation with malting quality phenotypes in barley (Hordeum vulgare L.) - Nora L. V. Lapitan; Ann Hess; Blake Cooper; Anna-Maria Botha; Deborah Badillo; Hari Iyer; Jolanta Menert; Timothy Close; Les Wright; Gary Hanning; M. Tahir; Christopher Lawrence (Theoretical and Applied Genetics, 2009)

Toward an integrated analysis of mitigation and adaptation: some preliminary findings - Thomas J. Wilbanks; Paul Leiby; Robert Perlack; J. Timothy Ensminger; Sherry B. Wright (Mitigation and Adaptation Strategies for Global Change, 2007)

The regional variation of aboveground live biomass in old‐growth Amazonian forests - YADVINDER MALHI; DANIEL WOOD; TIMOTHY R. BAKER; JAMES WRIGHT; OLIVER L. PHILLIPS; THOMAS COCHRANE; PATRICK MEIR; JEROME CHAVE; SAMUEL ALMEIDA; LUZMILLA ARROYO; NIRO HIGUCHI; TIMOTHY J. KILLEEN; et al. (Global Change Biology, 2006)
The biomass of tropical forests plays an important role in the global carbon cycle, both as a dynamic reservoir of carbon, and as a source of carbon dioxide to the atmosphere in areas undergoing deforestation. However, the absolute magnitude and environmental determinants of tropical forest biomass are still poorly understood. Here, we present a new synthesis and interpolation of the basal area and aboveground live biomass of old‐growth lowland tropical forests across South America, based on data from 227 forest plots, many previously unpublished. Forest biomass was analyzed in terms of two uncorrelated factors: basal area and mean wood density. Basal area is strongly affected by local landscape factors, but is relatively invariant at regional scale in moist tropical forests, and declines significantly at the dry periphery of the forest zone. Mean wood density is inversely correlated with forest dynamics, being lower in the dynamic forests of western Amazonia and high in the slow‐growing forests of eastern Amazonia. The combination of these two factors results in biomass being highest in the moderately seasonal, slow growing forests of central Amazonia and the Guyanas (up to 350 Mg dry weight ha −1 ) and declining to 200–250 Mg dry weight ha −1 at the western, southern and eastern margins. Overall, we estimate the total aboveground live biomass of intact Amazonian rainforests (area 5.76 × 10 6 km 2 in 2000) to be 93±23 Pg C, taking into account lianas and small trees. Including dead biomass and belowground biomass would increase this value by approximately 10% and 21%, respectively, but the spatial variation of these additional terms still needs to be quantified.

Vocal dialects, sex‐biased dispersal, and microsatellite population structure in the parrot Amazona auropalliata - TIMOTHY F. WRIGHT; ANGELICA M. RODRIGUEZ; ROBERT C. FLEISCHER (Molecular Ecology, 2005)
Geographic variation in microsatellite allele frequencies was assessed at nine sites in two regional vocal dialects of the parrot Amazona auropalliata (yellow‐naped amazon) to test for correspondence between dialects and population structure. There was no relationship between the genetic distances between individuals and their dialect membership. High rates of gene flow were estimated between vocal dialects based on genetic differentiation. In addition, 5.5% of pairs of individuals compared across the dialect boundary were estimated to be related at the level of half siblings, indicating that dispersal is ongoing. The number of effective migrants per generation between dialects estimated with the microsatellite data was roughly one‐seventh the number estimated with mitochondrial control region sequence data from the same individuals, suggesting that gene flow may be female‐biased. Together, these results suggest that the observed mosaic pattern of geographic variation in vocalizations is maintained by learning of local call types by immigrant birds after dispersal. We found no evidence that ongoing habitat fragmentation has contributed to cryptic population structure.

Haploinsufficiency of PAX9 is associated with autosomal dominant hypodontia - Parimal Das; David W. Stockton; Christopher Bauer; Lisa G. Shaffer; Rena N. D’Souza; Timothy J. Wright; Pragna I. Patel (Human Genetics, 2002)

Evidence that mesoaccumbens dopamine and locomotor responses to nicotine in the rat are influenced by pretreatment dose and strain - Timothy Iyaniwura; Adèle Wright; David Balfour (Psychopharmacology, 2001)

Nest Poaching in Neotropical Parrots - Timothy F. Wright; Catherine A. Toft; Ernesto Enkerlin‐Hoeflich; Jaime Gonzalez‐Elizondo; Mariana Albornoz; Adriana Rodríguez‐Ferraro; Franklin Rojas‐Suárez; Virginia Sanz; Ana Trujillo; Steven R. Beissinger; Vicente Berovides A.; Xiomara Gálvez A.; et al. (Conservation Biology, 2001)
Although the poaching of nestlings for the pet trade is thought to contribute to the decline of many species of parrots, its effects have been poorly demonstrated. We calculated rates of mortality due to nest poaching in 23 studies of Neotropical parrots, representing 4024 nesting attempts in 21 species and 14 countries. We also examined how poaching rates vary with geographic region, presence of active protection programs, conservation status and economic value of a species, and passage of the U.S. Wild Bird Conservation Act. The average poaching rate across all studies was 30% of all nests observed. Thirteen studies reported poaching rates of ≥20%, and four reported rates openface> 70%. Only six studies documented no nest poaching. Of these, four were conducted on islands in the Caribbean region, which had significantly lower poaching rates than the mainland Neotropics. The other two studies that showed no poaching were conducted on the two species with the lowest economic value in our sample ( U.S. retail price). In four studies that allowed direct comparison between poaching at sites with active nest protection versus that at unprotected sites, poaching rates were significantly lower at protected sites, suggesting that active protection efforts can be effective in reducing nest poaching. In those studies conducted both before and after the passage of the U.S. Wild Bird Conservation Act, poaching rates were found to be significantly lower following its enactment than in the period before. This result supports the hypothesis that the legal and illegal parrot trades are positively related, rather than inversely related as has been suggested by avicultural interests. Overall, our study indicates that poaching of parrot nestlings for economic gain is a widespread and biologically significant source of nest mortality in Neotropical parrots.